The role of type I interferons in regulating intestinal inflammation - Kole, A (2013)
Intestinal homeostasis is a delicate balance between suppression of immune responses against innocuous antigens and stimulation of immune responses against pathogens. Type I interferon (IFN-1) cytokines have both immunostimulatory and immunomodulatory effects. Colon mononuclear phagocytes (MP) constitutively produced IFN-1 in a TRIFdependent manner. We explored the function of endogenous IFN-1 in the colon using the T cell adoptive transfer model of colitis. Transfer of CD4+CD45RBhi naïve T cells from wild type (WT) or IFNAR subunit 1 knockout (IFNAR1-/-) mice into RAG-/- hosts resulted in similar onset and severity of colitis. In contrast, RAG-/- x IFNAR1-/- double knockout (DKO) mice developed accelerated severe colitis compared to RAG-/- hosts when transferred WT CD4+CD45RBhi T cells. Although WT or IFNAR1-/- regulatory T (Treg) cells equally prevented disease caused by CD45RBhi naïve T cells, WT Treg cells co-transferred with naïve CD4+ T cells into DKO recipients failed to expand or maintain Foxp3 expression and gained effector functions in the colon. IFNAR signaling on host hematopoietic cells inhibited T cell-mediated colitis, but not innate colitis. MPs isolated from the colon lamina propria (cLP) required IFNAR signaling for the production of the anti-inflammatory cytokines, IL-10, IL-27, and IL-1RA, but not for the production of classic pro-inflammatory cytokines. IFN-1-dependent secretion of IL-1RA was particularly important in inhibiting the migration of inflammatory DCs with potent T cell proliferative capacity from the cLP to the mesenteric lymph nodes. Finally, preliminary results suggested that IFN-1 may shape the commensal microbiota, but is not essential for controlling specific colitis-inducing bacteria.